2018
DOI: 10.1002/stem.2933
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Modulating Cancer Immunity with Hematopoietic Stem and Progenitor Cells

Abstract: Hematopoietic stem and progenitor cells (HSPCs) are the progenitor cells that can regenerate the entire blood compartment, including the immune system. Recent studies have unearthed considerable immune‐modulating potential of these cells. They can migrate through chemotactic gradients, differentiate into functional immune cells, and crosstalk with immune cells during infections, autoimmune diseases, and cancers. Although the primary role of HSPCs during solid malignancies is considered immunosuppressive, recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 89 publications
1
16
0
Order By: Relevance
“…Next, since tumor progression is associated with pronounced myelopoiesis (Wu et al, 2014), with the focus on the BM niche, we quantified myeloid and lymphoid cells in the BM compartment of naïve and tumor-bearing mice. Tumor-bearing mice exhibited an increase in myeloid cells and a decrease in lymphoid-derived B and T cells, in comparison to the tumor-free control group, in a comparable way to their changes in the tumor mass, as previously reported (Wildes et al, 2019). Importantly, the increased ratio of myeloid to lymphoid derived cells in the BM compartment was most pronounced in mice implanted with met-high tumors (Fig.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Next, since tumor progression is associated with pronounced myelopoiesis (Wu et al, 2014), with the focus on the BM niche, we quantified myeloid and lymphoid cells in the BM compartment of naïve and tumor-bearing mice. Tumor-bearing mice exhibited an increase in myeloid cells and a decrease in lymphoid-derived B and T cells, in comparison to the tumor-free control group, in a comparable way to their changes in the tumor mass, as previously reported (Wildes et al, 2019). Importantly, the increased ratio of myeloid to lymphoid derived cells in the BM compartment was most pronounced in mice implanted with met-high tumors (Fig.…”
Section: Resultssupporting
confidence: 87%
“…In fact, sustained met-high educated HSPC specific differentiation suggests the involvement of epigenetic modifications that might regulate their programming, a process that should be further elucidated. Furthermore, while there is an overwhelming amount of evidence for HSPCs giving rise to MDSCs in tumor conditions (Wildes et al, 2019), we found that LSK cells educated by met-low or met-high tumor conditions exhibit an MDSC phenotype, with specific differentiation program which further gives rise to M2 macrophages only in met-high tumors. Indeed, studies have demonstrated that myeloid cells and tumor-associated immunosuppressive macrophages (M2 macrophages) home to the pre-metastatic sites where they contribute to the recruitment and retention of circulating tumor cells (Condamine et al, 2015; Doak et al, 2018; Giles et al, 2016).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…1A). This combinatorial strategy strongly modulates the tumor microenvironment and promotes continued intratumor T-cell activation [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%